2012
DOI: 10.1029/2011jb008594
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamical triggering of slow slip on simulated earthquake faults with implications to Earth

Abstract: Among the most fascinating, recent discoveries in seismology are the phenomena of dynamically triggered fault slip, including earthquakes, tremor, slow and silent slip—during which little seismic energy is radiated—and low frequency earthquakes. Dynamic triggering refers to the initiation of fault slip by a transient deformation perturbation, most often in the form of passing seismic waves. Determining the frictional constitutive laws and the physical mechanism(s) governing triggered faulting is extremely chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 47 publications
(72 reference statements)
7
60
0
1
Order By: Relevance
“…The low effective normal stress of the fault zone being dynamically triggered is consistent with lab experiment of dynamic triggering of earthquakes (Johnson et al, 2012). The stress perturbations of 65-100 kPa associated with dynamic triggering of SSEs in this study are higher than the typical range of 1-5 kPa observed in studies of the dynamic triggering of earthquakes in volcanic/geyser regions in California (Aiken & Peng, 2014;Brodsky & Prejean, 2005) and nonvolcanic tremors near Parkfield (Peng et al, 2009), but comparable to the level of transient shear stresses (40-60 kPa) triggering nonvolcanic tremors in subduction zones (Rubinstein et al, 2007) and continental thrust faults (Peng & Chao, 2008).…”
Section: Conclusion and Discussionsupporting
confidence: 82%
“…The low effective normal stress of the fault zone being dynamically triggered is consistent with lab experiment of dynamic triggering of earthquakes (Johnson et al, 2012). The stress perturbations of 65-100 kPa associated with dynamic triggering of SSEs in this study are higher than the typical range of 1-5 kPa observed in studies of the dynamic triggering of earthquakes in volcanic/geyser regions in California (Aiken & Peng, 2014;Brodsky & Prejean, 2005) and nonvolcanic tremors near Parkfield (Peng et al, 2009), but comparable to the level of transient shear stresses (40-60 kPa) triggering nonvolcanic tremors in subduction zones (Rubinstein et al, 2007) and continental thrust faults (Peng & Chao, 2008).…”
Section: Conclusion and Discussionsupporting
confidence: 82%
“…This observation is similar to the previous results from the static triggering of frictional slip on filling gouges, such as the maximum shear stress of a fault zone under a static shear load increases with increasing normal stress [31]. The compaction state of filling gouges is thus importantly related to fault stability [2,32]. Additionally, we can observe that the frictional slip is partially recovered after a P-wave incidence ( Fig.…”
Section: Effect Of Normal Stresssupporting
confidence: 79%
“…Johnson and Jia [24] found that the dynamic triggering either further weakens a layer of filling gouges or induces the frictional slip when the gouge layer is near failure. The frictional slip is also related to the nonlinear dynamic response of filling gouges [2]. Furthermore, the dynamic triggering of frictional slip is a complex process that may be also associated with other factors, for instance, tectonic pressure, initial state of filling gouges and wave transmission and reflection from adjacent rock discontinuities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations